Life History of the Long-finned Pilot Whale (Globicephala melas edwardii); Insights From Strandings on the New Zealand Coast - Betty, Emma (Auckland University of Technology, 2019)
Extensive research has been conducted on long-finned pilot whale (Globicephala melas) populations in the North Atlantic, based predominantly on samples collected from drive fisheries. However, the species remains poorly understood in the Southern Hemisphere. Prior to this study, almost nothing was known of the biology or ecology of the unique long-finned pilot whale subspecies of the temperate south (G. m. edwardii). Despite recognition as data-poor by the International Union for the Conservation of Nature, G. m. edwardii has been classified as “Not Threatened” by the New Zealand Threat Classification System. Although pilot whales are not necessarily under threat, it can be argued that cetacean populations whose abundance, distribution, habitat use and life history remain unknown are most at risk, since population declines are likely to go unnoticed. G. m. edwardii mass strands frequently on the New Zealand coast and data collected from stranding events are the primary data for this population. This thesis contributes new understanding of the biology and ecology of this data-poor subspecies and identifies important relationships between mass stranding events and life history characteristics that have significant implications for the conservation of long-finned pilot whales in New Zealand waters. Specifically, this research presents novel information regarding: (1) growth rates, growth patterns/allometry, sexual dimorphism, (2) age structure, survival and mortality (3) male sexual maturation, (4) female reproductive parameters, and (5) spatiotemporal stranding patterns of G. m. edwardii on the New Zealand coast. Estimated length-at-birth, maximum size and age, survivorship, and average length and age at the attainment of sexual maturity are all reported to be lower in G. m. edwardii than in the North Atlantic subspecies (G. m. melas), indicating that geographic variation in life history occurs in this species, likely reflecting population-specific adaptation to local habitats. This study makes a significant contribution to the current scientific understanding of the poorly understood southern subspecies of the long-finned pilot whale, by providing the first life history data for G. m. edwardii in New Zealand waters.
Keywords: Long-finned pilot whale; Mass stranding; Reproduction; Growth; Cetacean; Conservation; New Zealand; Life history